2020
DOI: 10.1002/jbm.a.36878
|View full text |Cite
|
Sign up to set email alerts
|

The implication of the notch signaling pathway in biphasic calcium phosphate ceramic‐induced ectopic bone formation: A preliminary experiment

Abstract: Calcium phosphate (BCP) ceramic is a promising material in bone regeneration because it was proved biocompatible, osteoconductive, osteoinductive, and effective. Although it manifests favorable characteristics in critical‐sized bone defects repair, the mechanism of its osteoinduction is still unclear. In the present study, we studied the mechanism of ectopic bone formation, with interest in the Notch signaling pathway. BCP ceramics with or without Notch signaling inhibitor RO4929097 were cocultured with bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Studies have suggested that up‐regulation of the Notch signaling pathway promoted differentiation of BMSCs and significantly enhanced early bone formation 14 . When co‐culturing Sprague–Dawley (SD) rat BMSCs and BCP material, a significant up‐regulation in the expression of the Notch signaling pathway was detected in our previous study 15 . We found that the expression level of Notch1was up‐regulated about 30‐fold on the 1st, 4th, and 7th days of co‐culture (in vitro), meanwhile the overall expression levels of osteogenic genes were also up‐regulated.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Studies have suggested that up‐regulation of the Notch signaling pathway promoted differentiation of BMSCs and significantly enhanced early bone formation 14 . When co‐culturing Sprague–Dawley (SD) rat BMSCs and BCP material, a significant up‐regulation in the expression of the Notch signaling pathway was detected in our previous study 15 . We found that the expression level of Notch1was up‐regulated about 30‐fold on the 1st, 4th, and 7th days of co‐culture (in vitro), meanwhile the overall expression levels of osteogenic genes were also up‐regulated.…”
Section: Introductionmentioning
confidence: 72%
“…14 When co-culturing Sprague-Dawley (SD) rat BMSCs and BCP material, a significant up-regulation in the expression of the Notch signaling pathway was detected in our previous study. 15 We found that the expression level of Notch1was up-regulated about 30-fold on the 1st, 4th, and 7th days of co-culture (in vitro), meanwhile the overall expression levels of osteogenic genes were also up-regulated. Subsequently, after the addition of the Notch pathway inhibitor (RO4929097), the up-regulation was significantly inhibited, giving the conclusion that BCP can promote differentiation of BSMCs by upregulating the Notch signaling pathway and contributing to early osteogenesis.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the last decade, scaffold-based bone tissue engineering has gained increasing attention in various orthopaedic applications ( Sadiasa et al, 2013 ; Tao et al, 2019 ; Guo et al, 2020 ). It is a key scientific issue to prevent and cure ANFH by implanting bioactive materials combined with biologically active factors of key regulatory pathways ( Sharma et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%